Acute Kidney Injury due to Anticoagulant-Related Nephropathy : A Suggestion for Therapy. (8th June 2020) - Zeni, Letizia; Manenti, Chiara; Fisogni, Simona; Terlizzi, Vincenzo; Verzeletti, Federica; Gaggiotti, Mario; Cancarini, Giovanni
Abstract : The relationship between kidneys and anticoagulation is complex, especially after introduction of the direct oral anticoagulants (DOAC). It is recently growing evidence of an anticoagulant-related nephropathy (ARN), a form of acute kidney injury caused by excessive anticoagulation. The pathogenesis of kidney damage in this setting is multifactorial, and nowadays, there is no established treatment. We describe a case of ARN, admitted to our Nephrology Unit with a strong suspicion of ANCA-associated vasculitis due to gross haematuria and haemoptysis; the patient was being given dabigatran. Renal biopsy excluded ANCA-associated vasculitis and diagnosed a red blood cell cast nephropathy superimposed to an underlying IgA nephropathy. Several mechanisms are possibly responsible for kidney injury in ARN: tubular obstruction, cytotoxicity of heme-containing molecules and free iron, and activation of proinflammatory/proﬁbrotic cytokines. Therefore, the patient was given a multilevel strategy of treatment. A combination of reversal of coagulopathy (i.e., withdrawal of dabigatran and infusion of its specific antidote) along with administration of fluids, sodium bicarbonate, steroids, and mannitol resulted in conservative management of AKI and fast recovery of renal function. This observation could suggest a prospective study aiming to find the best therapy of ARN.